Using i-learn for online assessment: lecturers' perceptions / Ch'ng Pei Eng ... [et al.] - Ch'ng, Pei Eng; Hamat, Muniroh; Ng, Set Foong; Chew, Yee Ming; Omar, Mahanim (UiTM Cawangan Johor, 2018)
This paper describes a study carried out in Universiti Teknologi MARA to explore the lecturers' perceptions of online assessment. A survey questionnaire was administered on a sample of 40 full-time Computer and Mathematical Sciences lecturers in October 2017. The survey items focus on seven dimensions: (1) affective factors, (2) validity, (3) practical issues, (4) reliability and fairness, (5) security, (6) pedagogy issues and (7) the intention to conduct online assessment. The aim of the survey was to investigate lecturers' perceptions of using i-Learn as assessment tool and to analyze whether their perceptions differ based on their area of specialization. The findings of the survey indicate that i-Learn online assessment tool was under used and the lecturers' intentions to conduct online assessment are still very low. Their main concern is generally due to the nature of the subject taught which they think it is not appropriate to be tested online. Besides that, issues related to system security, cheating in digital age, and multiple-choice type of test items were some factors that hindered them from adopting online assessment. Lastly, the paper concludes that i-Learn does not fully addressed the critical need of Computer and Mathematical Sciences lecturers in order for them to adopt and increase their use of online assessment in their courses. Furthermore, perhaps the training module for this group of lecturers should be redesigned to expose them how to design the new test items which can assess on the higher order thinking skills.